2017
DOI: 10.13075/ijomeh.1896.00797
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic predictors of person–organization fit

Abstract: Objectives: The aim of this study was to explore the relationship between socio-demographic characteristics and the level of complementary and supplementary person-organization fit (P-O fit). Material and Methods: The study sample was a group of 600 Polish workers, urban residents aged 19-65. Level of P-O fit was measured using the Subjective Person-Organization Fit Questionnaire by Czarnota-Bojarska. The binomial multivariate logistic regression was applied. The analyzes were performed separately for the men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Dorota and Andysz analysed fifteen socio-demographic variables and work characteristics that could impact P-O fit and found that only a few were significantly associated with P-O fit such as social relationships, time demands, work shifts schedule systems, depression, health and functioning, employment history etc. They also found that demographic variables in general were not an important predictor of good P-O fit for both the genders [33].…”
Section: Introduction and Reviewmentioning
confidence: 94%
“…Dorota and Andysz analysed fifteen socio-demographic variables and work characteristics that could impact P-O fit and found that only a few were significantly associated with P-O fit such as social relationships, time demands, work shifts schedule systems, depression, health and functioning, employment history etc. They also found that demographic variables in general were not an important predictor of good P-O fit for both the genders [33].…”
Section: Introduction and Reviewmentioning
confidence: 94%
“…For instance, HRM practices (e.g., training, compensation, development, and growth opportunities ( Kakar et al, 2019b ; Uppal, 2020 ; Samad et al, 2022 ), and organizational support ( Tseng and Yu, 2016 ) have an important effect on PJF. Similarly, long working hours ( Merecz-Kot and Andysz, 2017 ) and work demands, among other factors, have a significant impact on PJF.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…A majority of studies devoted to the predictors of person-organization fit have revolved around the role of individual characteristics such as personal traits, values and professional competencies (Merecz-Kot and Andysz, 2017). Person-organization fit is related to several outcomes including work performance and work attitudes, turnover, teamwork effectiveness, organizational citizenship behaviors, creativity, stress and well-being (Merecz-Kot and Andysz, 2017).…”
Section: Ethical Leadershipmentioning
confidence: 99%